Identifying the Support of Human Resource Specialists to Facilitate the Learning of Education Workers in Hormozgan Province - Ahad Ameri; Mohammadnoor Rahmani; Leila Khajehpour (Iranian Journal of Educational Research)
Objective: Education staff professional development is a comprehensive, focused and supportive approach designed to promote education staff for growth. The aim of the present study was to identify the support of human resource specialists in facilitating the learning of education workers in Hormozgan province. Methods: The research method was qualitative and the studied population was education workers of Hormozgan province, 14 of them were selected as a sample by snowball sampling. An interview was used to collect data, and its validity was confirmed by experts. Strauss and Corbin coding method was used to analyze the data obtained from the interviews. Results: The findings showed that the results of the analysis of the interviews showed that human resource specialists, as representatives of the organization in the training unit, play the role of facilitating and supporting people's learning. These professionals can provide six types of support needed for learning, including providing information resources, funding, job promotion, financial and non-financial incentives, executive support, and networking. Conclusions: The findings generally showed that human resource professionals can use the necessary learning supports provide the basis for more effective learning to be implemented in the organization.